Integrasi Islam dan Sains dalam Pemikiran Ismail Raji Al-Faruqi, Seyyed Hossein Nasr, Al-Ghazali, dan Ibnu Khaldun: Pendekatan Iman, Islam, dan Ihsan Berdasarkan Al-Qur'an, Hadits, dan Qoul Ulama - Afifah Agustini; Ainur Rofiq Sofa (Jurnal Budi Pekerti Agama Islam, 2024)
This study examines the integration of Islam and science through the thoughts of key figures, namely Ismail Raji Al-Faruqi, Seyyed Hossein Nasr, Al-Ghazali, and Ibnu Khaldun. The main focus of this research is to understand their approaches to the relationship between religion and knowledge, highlighting key concepts such as iman (faith), Islam, and ihsan (excellence). This approach is explained based on primary sources such as the Qur'an, Hadith, and qoul ulama, which provide the philosophical and theological foundation for understanding the integration of both. Using a qualitative approach, this research aims to explore how these perspectives shape a balanced view between the scientific and spiritual realms within the context of Islamic thought. The results of the study show that although each figure has a different viewpoint, they agree that science does not conflict with Islamic teachings; rather, it should be understood as a means of drawing closer to God. This research is expected to contribute to the development of dialogue between religion and science, as well as provide insights into the development of Islamic education in the modern era.